DIGITALIZATION AS A LEVER OF INNOVATION FOR SMES: AN EXPLORATORY STUDY IN THE CAMEROONIAN CONTEXT - Djeudja, Rovier; Matejang, Letissia Stephanie; Nya, Magloire Tchatchoua (Copernican Journal of Finance & Accounting, 2023)
The objective of this study is to examine the influence of digitalization on innovation in Cameroonian firms. For this purpose we used the main variables of digitalization, namely ICT and digital technologies, to better explain innovation, whether it be process, product or organizational. To achieve this, the empirical verification was carried out through qualitative data processing analyses such as: descriptive data analysis and MCA (Multiple Correspondence Analysis) method. This qualitative methodological approach enabled us to survey 20 Cameroonian SMEs with different characteristics during the year 2020. The study shows that digitalization has a significant influence, with positive externalities on the innovation of companies. The answers collected show that the adoption and introduction of digital tools in the exercise of the company’s activities leads to the reinvention of the company’s traditional management models. The originality of our work lies in the fact that the study attempts to use a qualitative method to question the relationship between digitalization and innovation in Cameroonian SMEs.